Knowledge of Dentists regarding Antibiotic Prescription in Endodontics in Tripoli - Soltan, Fatma; Asma Abognah; Haneen Azzuz (Khalij-Libya Journal of Dental and Medical Research, 2024)
The aim of this study was to assess how well dentists understand and follow guidelines for prescribing antibiotic in endodontics in Tripoli. A questionnaire link was sent to all participants via various social media platforms. All answers from the online form were automatically imported in an Excel file and were then appropriately analyzed. Descriptive statistics (such as frequencies and percentages) were calculated, and Chi-square test were used to compare between the groups. The majority (67.6%) of the respondents were general dental practitioners and most of them were females (80.4%). A smaller group (10.8%) were endodontic specialists while 21.6% belong to other specialties. Diffuse swelling was the most common condition for which antibiotics were prescribed (81.4%) and in patient with swelling & difficulty in swallowing (73.5%). Antibiotics were always prescribed by 65,7% of respondents for patient exhibiting systemic symptoms such as fever and malaise and 6.9% of respondents always prescribed antibiotics in prolonged root canal treatment. The Majority of respondents selected Amoxicillin with Clavulanate as the first choice for patients without medication allergies (72.7%) and Amoxicillin ranked as the second most preferred antibiotic (39.4%) (Table 3). On the other hand, the majority of respondents preferred clindamycin as the first choice for patients with penicillin allergy (43.6%). The majority of the participants believe that the typical duration of antibiotics course is five to seven days (98%). The majority (95.1%) of respondents were aware of drug resistance, while a very small percentage (4.9%) were not aware. The data reveal that critical importance of selecting antibiotics based on patient-specific factors, such as allergies, to ensure effective and safe management of endodontic infections. The knowledge and attitude of dentists regarding antibiotic prescription for endodontic treatments require further improvement. كان الغرض من هذه الدراسة هو التحقق من معرفة أطباء الأسنان فيما يتعلق بوصف المضادات الحيوية في علاج جذور الأسنان في طرابلس. تم إرسال رابط استبيان الى جميع المشاركين عبر منصات التواصل الإجتماعي المختلفة. تم جمع البيانات و تحليلها احصائيا. كانت الغالبية من المشاركين (67.6%) أطباء أسنان عام و كان معظمهم من الإناث (80.4%). كان التورم المنتشر هو الحالة الأكثر شيوعا لوصف المضادات الحيوية (81.4%), كما كانت المضادات توصف للمرضى الذين يعانون من تورم و صعوبة في البلع (73.5%). حيث وصف 65.7% من الآطباء المضادات الحيوية للمرضى الذين يعانون من أعراض مثل الحمى و التوعك. اختار ْأغلبية المستجيبين الأموكسيسيلين مع كلافونات كخيار أول للمرضى الذين لا يعانون من حساسية اتجاه البنسلين (72.7%), بينما فضلت الغالبية الكلينداميسين كخيار أول للمرضى الذين يعانون من حساسية للبنسلين (43.6%). أظهر غالبية المشاركين أن المدة النموذجية للمضادات الحيوية تتراوح بين خمسة الى سبعة أيام (98%). كشفت البيانات الأهمية الحيوية لإختيار المضادات الحيوية بناء على العوامل الخاصة بالمرضى, مثل الحساسية, لضمان علاج فعال و امن للعدوى في علاج جذور الأسنان مما يتطلب تحسين المعرفة لدى أطباء الأسنان فيا يخص وصف المضادات الحيوي